Determinants of hypertension-related knowledge, attitude, and practices (KAP) among caregivers in Neno, rural Malawi: A cross-sectional study - Chikondi Maluwa; Sitalire Kapira; Hataichanok Chuljerm; Wason Parklak; Kanokwan Kulprachakarn (Heliyon)
Background: Hypertension, a significant health concern, increases the risk of cardiovascular disease and premature mortality. Caregivers play a crucial role in ensuring optimal care for hypertensive patients and reducing associated complications. Caregivers' basic knowledge, good attitude, and relevant practices are necessary to ensure high-quality care for patients with hypertension. However, there is no research conducted in Malawi that investigated the knowledge, attitude, and practices of caregivers towards hypertension prevention and management. Objective: The study aimed to assess knowledge, attitude, and practices towards hypertension and their determinants among caregivers of hypertensive patients in Neno, Malawi. Methods: Our study, conducted in Neno, Malawi, involved 422 caregivers of hypertensive patients. We used a cross-sectional study design. Data was collected through a structured questionnaire and analyzed using SPSS Version 22.0. Results: The participants had a mean age of 44.94 years (SD = 9.889), with 63.3 % being female. The mean KAP scores were 38 %, 93.3 %, and 78.7 %, respectively. Positive correlations were found between knowledge and practice (r = +0.252; p < 0.001) and knowledge and attitude (r = +0.255; p < 0.001). However, no significant relationship was observed between attitude and practice (r = +0.064; p = 0.190). Age showed a strong correlation with attitude (r = +0.233; p < 0.001) but not with knowledge or practice. On the other hand, occupation, education level, and caregiver-patient relationship significantly influenced knowledge and attitude but not practice. Gender also demonstrated a notable association with KAP regarding hypertension. Conclusion: Caregivers demonstrated poor knowledge but engaged in good practices. Despite their limited understanding, they maintained an excellent attitude towards hypertension. This highlights the necessity for increased prevention, and control strategies within communities, emphasizing health education on lifestyle modifications and to address the gaps identified in caregivers’ understanding in the prevention and management of hypertension.